2003
DOI: 10.1149/1.1627353
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organic Contamination on the Electrical Degradation of Hydrogen-Terminated Silicon upon Exposure to Air under Ambient Conditions

Abstract: The degradation of the electrical characteristics of hydrogen-terminated silicon ͑both n-and p-doped͒ under typical laboratory environments was investigated. When a hydrogen-terminated silicon ͑H-Si͒ surface was exposed to air under ambient conditions, the current density/bias voltage ͑J-V͒ curve of the mercury-silicon junction thus formed changed significantly during the first 50 h. For n-type H-Si surfaces, the J-V curve initially maintained ohmic characteristics for a period of 8-12 h, then evolved to diode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 38 publications
3
12
0
Order By: Relevance
“…We note that the careful cleaning and drying steps involved before each measurement reduces such a possibility. Our previous studies revealed that cleaning hydrogen-terminated silicon with organic solvents after being exposed to ambient conditions can remove surface contamination effectively (as evidenced by both infrared spectroscopic and electrical measurements). , It has been previously shown that small amounts of oxidation significantly modify the optical properties of H−Si (Δ value changes); ,, the oxide growth occurring within the “pinholes” on unreacted silicon (Scheme ) would likely change the observed ellipsometric angles (Ψ, Δ), which leads to inaccurate modeling of the monolayer thickness. We believe that the construction of a more accurate model for the partially oxidized silicon−monolayer interface instead of the simple silicon−organic two-layer protocol is necessary.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We note that the careful cleaning and drying steps involved before each measurement reduces such a possibility. Our previous studies revealed that cleaning hydrogen-terminated silicon with organic solvents after being exposed to ambient conditions can remove surface contamination effectively (as evidenced by both infrared spectroscopic and electrical measurements). , It has been previously shown that small amounts of oxidation significantly modify the optical properties of H−Si (Δ value changes); ,, the oxide growth occurring within the “pinholes” on unreacted silicon (Scheme ) would likely change the observed ellipsometric angles (Ψ, Δ), which leads to inaccurate modeling of the monolayer thickness. We believe that the construction of a more accurate model for the partially oxidized silicon−monolayer interface instead of the simple silicon−organic two-layer protocol is necessary.…”
Section: Resultsmentioning
confidence: 99%
“…To quantify the J − V properties and gain insight into the current transport mechanism through the junctions, the classical thermionic emission theory, a majority carrier model, has been frequently applied with varying degrees of success ,,,,,, ln true[ J 1 e q V / k T true] = ln ( A * T 2 ) q ϕ eff k T + q V n k T where J is the measured current density, V the applied bias, A * the Richardson constant (110 A·cm −2 ·K −2 ), ϕ eff the effective barrier height, ,,,, q the electronic charge, k the Boltzmann’s constant, T the absolute temperature, and n the ideality factor. On the basis of the above equation, we would expect a linear relationship between ln J and V , and a change in the J − V curve at a low-forward bias would yield different values of ϕ eff and n .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several groups measured the current-voltage ͑I − V͒ characteristics for hydrocarbon monolayers with a liquid Hg electrode, [6][7][8][9][10][11][12][13][14][15][16] because Hg contacts softly and homogeneously with SAMs. 6,[8][9][10][11][12][13][14]16,19 On the other hand, Ohmic contacts were achieved for Hg/hydrogen-terminated n-type Si structures, 6,15,16,20 because the electron affinity of the hydrogen-terminated n-Si and the workfunction of Hg are energetically close. 6,[8][9][10][11][12][13][14]16,19 On the other hand, Ohmic contacts were achieved for Hg/hydrogen-terminated n-type Si structures, 6,15,16,20 because the electron affinity of the hydrogen-terminated n-Si and the workfunction of Hg are energetically close.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, studies of a few organic contaminants on silicon wafers have been carried out by identifying contaminants by thermal desorption-gas chromatography/mass spectroscopy (TD-GC/MS), 6,7 time of flight-secondary ion mass spectroscopy (TOF-SIMS), 8 X-ray photoelectron spectroscopy (XPS), 9 and Fourier transform-infrared spectroscopy (FT-IR). 10 The phenomenon has been explained by postulated degradation mechanisms but the causes of the device failure due to the organic contamination have not been experimentally studied.…”
Section: Introductionmentioning
confidence: 99%